2001
DOI: 10.1111/j.1572-0241.2001.04668.x
|View full text |Cite
|
Sign up to set email alerts
|

Small intestinal bacterial overgrowth in patients with cirrhosis: prevalence and relation with spontaneous bacterial peritonitis

Abstract: Small intestinal bacterial overgrowth in cirrhotic patients is associated with acid-suppressive therapy and hypochlorhydria, but not with spontaneous bacterial peritonitis. The potential role of acid-suppressive therapy in the pathogenesis of spontaneous bacterial peritonitis merits further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
63
1
5

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 229 publications
(75 citation statements)
references
References 27 publications
6
63
1
5
Order By: Relevance
“…More recently, the chronic use of PPI has been associated with community-acquired Clostridium difficile colitis [11] and a meta-analysis found an association with acid suppression and enteric infection [12]. Similarly, in two retrospective human studies, the crude odds ratio for development of spontaneous bacterial peritonitis among PPI users versus nonusers ranged from 1.22 to 7.0 [8,13]. A human study by Narula et al found that transgastric instrumentation contaminates the peritoneal cavity and those patients on PPIs have a higher bacterial load compared with nonusers [7].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the chronic use of PPI has been associated with community-acquired Clostridium difficile colitis [11] and a meta-analysis found an association with acid suppression and enteric infection [12]. Similarly, in two retrospective human studies, the crude odds ratio for development of spontaneous bacterial peritonitis among PPI users versus nonusers ranged from 1.22 to 7.0 [8,13]. A human study by Narula et al found that transgastric instrumentation contaminates the peritoneal cavity and those patients on PPIs have a higher bacterial load compared with nonusers [7].…”
Section: Discussionmentioning
confidence: 99%
“…Increased fecal counts of streptococci, comparable to those of coliforms, and a high prevalence of small intestinal bacterial overgrowth with Gram-positive bacteria have been reported in patients with cirrhosis. [24][25][26] Increased extraintestinal translocation of Gram-positive bacterial antigens would be expected in such circumstances, given experiences in experimental animals. 43,44 Indeed, lipoteichoic acid, a component of Gram-positive bacteria, has recently been found in liver tissue of cirrhotic patients, presumably as a consequence of extraintestinal translocation from the gut lumen.…”
Section: Discussionmentioning
confidence: 99%
“…In cirrhotic patients, in addition, there is bacterial overgrowth in the small intestine. [11][12][13][14][15] Bacteria deconjugate bile acids, 16 and bacterial deconjugation should result in a further reduction in bile acid concentration because unconjugated bile acids are rapidly absorbed by nonionic diffusion. Finally, studies have indicated there is increased small intestinal permeability in cirrhosis, [17][18][19][20] raising the possibility that even conjugated bile acids, which are membrane-impermeable in health, might be absorbed passively.…”
mentioning
confidence: 99%